Rancang Bangun Aplikasi Pengelolaan Keuangan Berbasis Android Menggunakan Framework React Native - Harry, Soepandi; Wijonarko, Dwi; Afif, Hasnan (INFORMAL: Informatics Journal, 2023)
Financial management application is an information system that facilitates the organization to manage financial data for related fields so that it can help complete activities in the financial sector, especially for the process of recording and financial statements quickly. The aim is to realize the Implication of a android-based Financial Information System to support the presentation of information in the decision-making process by the leadership, as well as the finance department. The method used is analytical methods and design methods. The design method is making the implementation of information systems, database design and financial data analysis. The method of analysis is done by using observation and interview techniques, literature studies, direct surveys at de.Blado Coffee & Tea by interviewing related people to complete the information needed. The end result of implementing a android-based financial information system is used to simplify and speed up data access and provide the leadership with full access to data without processing operational data. With the establishment of information systems, structured and integrated data can be produced well as input for management in the decision making process.